Who do they think they are: Making sense of self in residential care, foster care, and adoption. (October 2019) - Neagu, Mariela; Sebba, Judy
Abstract : Abstract: This article explores how the type of placement in children's social care influences identity formation and contact with the birth family. It draws on 40 life history interviews with Romanian-born, care experienced young people who entered adulthood from different types of placement: 16 from residential care, eight from foster care, seven from domestic adoption and nine from intercountry adoption. The article contributes to an understanding of how residential care, foster care, domestic adoption and intercountry adoption affect identity formation and contact with the birth family from the perspectives of those who lived them, the challenges they encountered and the strategies they adopted to make sense of who they were during adolescence and transition to adulthood. The findings suggest that all the research participants had met or wanted to meet their birth families, and that stigmatisation occurred in all types of placement. The type of placement they were in influenced the support or the challenges they faced when they wanted to gain knowledge of their birth families and the circumstances in which they met their birth family. In some cases, their intention to search for the birth family led to tensions or conflict between them and their adoptive or foster carers. However, this study suggests that knowledge of, and contact with their birth family did not modify the quality of the children's relationship with them (foster carers or adoptive parents). It also suggests that when raised by carers other than their birth parents, children allocate parental roles to carers or other significant adults and that challenges related to identity formation in adolescence differ between residential care, foster care and adoption. Highlights: All types of placement interfere with identity formation; Knowledge of the birth family was accessed differently in different types of placement. In adoption, knowledge of the birth family did not change the relationship with their adoptive parents. Stigmatisation was reported in relation to every type of placement. Most participants placed in residential care at birth reported no romantic relationships.